Associations between stressors and difficulty sleeping in critically ill patients admitted to the intensive care unit: a cohort study - Roberto Carlos Miranda-Ackerman; Mariana Lira-Trujillo; Alma Carolina Gollaz-Cervantez; Ana Olivia Cortés-Flores; Carlos José Zuloaga-Fernández del Valle; Luis Alberto García-González; Gilberto Morgan-Villela; Francisco José Barbosa-Camacho; Kevin Josue Pintor-Belmontes; Bertha Georgina Guzmán-Ramírez; Aldo Bernal-Hernández; Clotilde Fuentes-Orozco; et al. (BMC, 2020)
Abstract Background Patients admitted to the intensive care unit (ICU) experience sleep disruption caused by a variety of conditions, such as staff activities, alarms on monitors, and overall noise. In this study, we explored the relationship between noise and other factors associated with poor sleep quality in patients. Methods This was a prospective cohort study. We used the Richards-Campbell Sleep Questionnaire to explore sleep quality in a sample of patients admitted to the ICU of a private hospital. We measured the noise levels within each ICU three times a day. After each night during their ICU stay, patients were asked to complete a survey about sleep disturbances. These disturbances were classified as biological (such as anxiety or pain) and environmental factors (such as lighting and ICU noise). Results We interviewed 71 patients; 62% were men (mean age 54.46 years) and the mean length of stay was 8 days. Biological factors affected 36% and environmental factors affected 20% of the patients. The most common biological factor was anxiety symptoms, which affected 28% of the patients, and the most common environmental factor was noise, which affected 32.4%. The overall mean recorded noise level was 62.45 dB. Based on the patients' responses, the environmental factors had a larger effect on patients' sleep quality than biological factors. Patients who stayed more than 5 days reported less sleep disturbance. Patients younger than 55 years were more affected by environmental and biological factors than were those older than 55 years. Conclusions Patient quality of sleep in the ICU is associated with environmental factors such as noise and artificial lighting, as well as biological factors related to anxiety and pain. The noise level in the ICU is twice that recommended by international guides. Given the stronger influence of environmental factors, the use of earplugs or sleeping masks is recommended. The longer the hospital stay, the less these factors seem to affect patients' sleep quality.